The Impact of Work Environment, Work Relation and Compensation to Trainees’s Productivity in The Stones – Legian, Bali – A Marriott Autograph Collection Hotel - Sugisna, Darmajaya; Ariani, Ni Made; Rahyuda, Irma (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 3 (2018): Vol.2,No.3,2018, 2019)
Tourism is one of highest growth sector in Indonesia and Bali especially. The Increased of tourist visited impact the increased of accomodation which also increased the labor needs. The Syncronization needed to prospective workers joining accomodation sector by on the job training programs. Trainee which did on the job training needs well work atmosphere so they could learn and give productivty, which is showed by quality of worklife concept. Therefore, not all part of quality of worklife suits the trainee situation, which in this research only took work environment, work relation and compensation as variabel. This research held in The Stones – Legian, Bali – A Marriott Autograph Collection Hotel, using 3 independent variabel, which is work environment (X 1 ), work relation (X 2 ) and compensation (X 3 ). The datas got by observations, interview, literature studies, online questionnaire and documentations. Respondens are 59 trainees. This Research using multiple linear regression to find impact of independent variabel to dependent by partialy or simultaneously. The test gave results t count of work environment (X 1 ) 0,510, work relation (X 2 ) 2,934 and compensation (X 3 ) 1,422 with the t table value is 2,004. Therefore, Simultaneously X’s Variabel got 11,211 F count with F table 2,11 and determination coefficents is 37,9%. Conclusion for the research are only work relation variabel (X 2 ) significantly impacts trainee’s productivity, which work environment (X 1 ) and compensation (X 3 ) doesn’t give significantly impact. Also there are simultaneously impacts of  X’s Variabels to the Y’s Variabel.